PERAN BRAND IMAGE DALAM MEMEDIASI PENGARUH ELECTRONIC WORD OF MOUTH TERHADAP NIAT BELI - Ari Suyoga, Ida Bagus Gede; Santika, I Wayan (E-Jurnal Manajemen, 2018)
Food is an important thing becuase is a basic human need. Richeese Factory is a fast food restaurant from Indonesia with a menu of spicy fried chicken with cheese sauce which is a subsidiary of Kaldu Sari Nabati. This study aims to explain the role of brand image in mediating the influence of electronic word of mouth on the purchase intention of Recheese Factory products in Denpasar. Data collection in this study using questionnaires. The number of samples is 100 respondents and using non-probability sampling technique. The analysis technique used in this research is path analysis technique Based on the results of the analysis found that electronic word of mouth has a positive and significant effect on purchasing intentions. Brand image has a positive and significant influence on buying intentions. Brand positive and significant image mediates the influence between electronic word of mouth on buying intentions. Suggestions that can be given based on the results of research is Richeese Factory should further increase innovation and open more branches so that will provide more positive dampat or benefits for consumers to better know the products owned Richeese Factory.